Non-Verbal Categories. Analysis of an Galician Oral Narrative - Rivas, Aitor (Madrygal. Revista de Estudios Gallegos, 2015)
Based on the concept of the triple basic structure of human communication by Poyatos (1994a, 1994b) and on the analytical and theoretical implications that derive from this, the present paper conceives the human communication as an indivisible whole in which verbal communication can not be separated from body behavior. This paper analyzes nonverbal categories used in oral communication. The corpus consists of an oral narration in Galician from which we highlighted certain kinemes (minimum units of body movement with meaning) by using the model proposed by Bouvet (2001), in order to explain the non-verbal categories with examples taken from said recordings.